Understanding the structure-activity relationship of additives for durable Zn metal batteries: a case study of aromatic molecules - Cai, Da-Qian (2025)
Detrimental dendrite growth and parasitic side reactions greatly hinder the practical application of aqueous metal batteries. Despite many reports on exploring electrolyte additives to mitigate the above issues, the structure-activity relationship of the additives in terms of their adsorption configurations and anti-dendrite/corrosion effects has been rarely considered, especially when the additive concentration is sufficiently low. Herein, by taking the members of aromatic Lewis base molecules as a study case, we found that there exists an optimal adsorption configuration (determined by the position of -N sites) for the additive to synchronously supply abundant zincophilic sites to accelerate Zn2+ desolvation and guide uniform Zn nucleation without hydrogen evolution. As a result, the lifespan of both the Zn symmetric cell and Zn||NVO full cell achieve long-term cycle stability. This work may shed light on the additive design for not only Zn but also other alkaline metal anodes in aqueous energy storage systems.